Computertomographie bei Patienten mit stabiler Angina Pectoris: Messung der fraktionellen Flussreserve = Computed tomography in patients with chronic stable angina : fractional flow reserve measurement - Renker, Matthias; Becher, Tobias; Henzler, Thomas; Borggrefe, Martin; Akın, Ibrahim; Baumann, Stefan (Herz, 2017)
Coronary computed tomography angiography (cCTA) has been established for the non-invasive diagnosis of coronary artery disease (CAD). Previous studies demonstrated the high diagnostic accuracy of cCTA, particularly for ruling out CAD. As a known limitation of cCTA a large number of visually significant coronary stenoses are found to be hemodynamically not relevant by invasive fractional flow reserve (FFR). CT-based FFR (CT-FFR) builds on recent advances in computational fluid dynamics and image simulation techniques. Along with CT myocardial perfusion imaging, CT-FFR is a promising approach towards a more accurate estimation of the hemodynamic relevance of coronary artery stenoses. CT-FFR is derived from regular CT datasets without additional image acquisitions, contrast material, or medication. Two CT-FFR techniques can be differentiated. The initial method requires external use of supercomputers and has gained approval for clinical use in the USA. Furthermore, a prototype-software has been introduced which is less computationally demanding via integration of reduced-order models for on-site calculation of CT-FFR. The present article reviews these methods in the context of available study results and meta-analyses. Furthermore, limitations and future concepts of CT-FFR are discussed.